The tangent objective - Sanders, Lawrence, 1920- (New York : Putnam, 1976)
As the corrupt and strife-torn African nation of Asante teeters on the brink of savage revolt, the lives of two men -- one white, one black are caught tip in an explosive maelstrom of money, politics, intrigue and violent reaction.
Keywords: Africa -- Politics and government -- Fiction; Detective and mystery stories; Political fiction